The Effect of Water Stress on Tuber Formation in Potato Plants - Sinulingga, Elpiani; Nurhayati, Nurhayati; Ritonga, Sri Hafnida; Aditya Sari, Ruri (Demeter: Journal of Farming and Agriculture, 2024)
Potato (Solanum tuberosum L.) is often considered a drought-sensitive crop, and its sustained production is increasingly threatened by frequent drought events. Drought presents one of the most significant challenges to potato production worldwide. Plants experience water stress when the water they receive is insufficient to meet their actual needs. The effects of drought stress range from disruptions at the molecular and biochemical levels within cells to physiological and morphological impairments at the leaf and whole-plant levels. Potato plants are particularly vulnerable to drought due to their shallow root systems. As a result, climate change is expected to have a considerable impact on global potato production, as limited water availability can significantly reduce tuber yield. Potato plants respond to drought stress through various physiological, biochemical, and molecular strategies. This review compiles research findings to better understand the impact of water stress on tuber formation, the mechanisms through which drought stress affects potato plants, the plant's resistance responses, and strategies to mitigate the effects of drought stress in potatoes.